INVESTIGATION OF GROUNDWATER POTENTIAL ZONES USING ELECTRICAL RESISTIVITY METHOD IN MUBI SOUTH LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NORTH EASTERN NIGERIA. Issue 1 (2021) - Sunday, A.; Usman, A.
No abstract available